Lithostratigraphy of the Prince Edward Island redbeds - van de Poll, H. W. (Atlantic Geoscience, 1989)
The redbeds of Prince Edward Island are of Stephanian-late Early Permian age and represent the youngest known on-land exposed strata of uk post (Acadian) orogenic Maritimes Basin of eastern Canada. The Island redbeds have previously been informally subdivided into four Fining-upwards megacyclic sequences I, II, HI and IV, on the basis of variations in grain size and composition. It has also been past practice to informally assign the redbeds to the top of the Pictou Group of Nova Scotia and New Brunswick with which they merge uninterruptedly at depth below the Island. Regional variations in conglomerate composition, maturity and sediment dispersal trends indicate tiiat the redbeds comprise two separate lithofacies sequences representing: (1) die relative distal platformal Pictou Group lithofacies of New Brunswick to the southwest, and (2) the more proximal Cumberland Sub-basin Pictou Group lithofacies of Nova Scotia to the south. It is suggested here that lithostratigraphic purpose may be best served by die following changes: The Northumberland Strait Supergroup be established to accommodate die Pictou Group below (grey and red terrestrial strata, locally coal measures) and the Prince Edward Island Group (redbeds) above. The Prince Edward Island Group is to be subdivided on the basis of their internal megacyclic order into five formal formations and two members. From oldest to youngest these are: Miminegash, Egmont Bay, Kildare Capes, Hillsborough River and Orby Head formations. The Hillsborough River Formation is further subdivided into die Malpeque and Wood Islands members. The Stephanian-late Early Permian age of the Prince Edward Island redbeds is reasonably well established on the basis of paleontological evidence. RÉSUMÉ Les séries rouges de L’lie du Prince-Edouard, d’âge compris entre le Stéphanien et la Fin du Permien précoce, représentent les plus jeunes strates connues du Bassin post-orogénique (post-acadien) des Maritimes à affleurer sur la lerre ferme. On a auparavant subdivisé ces séries de façon informelle, en raison de variations dans leur granuloma trie et leur composition, en quatre mégaséquences granodecroissantcs (I, II, HI et IV). H était aussi coutume d’attribuer de façon informelle ces séries rouges au sommet du Groupe de Pictou (Nouvelle-Écosse et Nouveau-Brunswick), auquel elles s’incorporent continument, et ce en profondeur sous l’ile. Les variations régionales dans la composition des poudingues, la maturité des sédiments ainsi que les tendances dans la dispersion des sédiments démontrent que les assises rouges s’articulentendeux séries distinctesde lithofaciès représentant (1) vers le sud-ouest (Nouveau-Brunswick), le lithofaciès de plate-forme plus externe du Groupe de Pictou et (2) vers le sud (Nouvelle-Écosse), le lithofacèis plus proximal du Sous-Bassin de Cumberland dans le Groupe de Pictou. On suggère que la lithostratigraphie serai t favorisée par les changements suivants: que le Supergroupe de Northumberland Strait soit établi pour concilier en bas le Groupe de Pictou (strates terrestres grises et rouges, veines de charbon locales) et en haut le Groupe de Prince Edward Island (séries rouges). On subdivise de façon formelle le Groupe de Prince Edward Island en cinq formations et deux membres en s’appuyant sur leur disposition mégacyclique interne. De la plus vieille à la plus jeune, celles-ci englobent les formations de Miminegash, d’Egmont Bay, de Kildare Capes, de Hillsborough River et d’Orby Head. On subdivise aussi la Formation de Hillsborough River en deux membres: les membres de Malpeque et de Wood Islands. L’âges stéphanien-éopermien tardif des assises rouges de l’ile du Prince-Edouard est raisonnablement établi sur des bases paléontologiques. [Traduit par le journal]